‘TOUCHED’ BY HUMOUR IN LIFE: CHARACTERS IN JOHN MCGAHERN’S FICTION - Radler, Dana (Transfer. Reception Studies, 2020)
In John McGahern’s stories, stories bring to life characters in both comic and tragic instances, and their whole existence comes under the spotlight, as the writer uses mild, ironic or sarcastic touches. In between automatisms and mobility often directed at dogmatism or mental stereotypes displayed by characters, clergymen, workers, teachers, writers or family members display their ignorance, occasional (lack of) manners, boredom or elevation, often imitating what seems to be ‘decent’ in terms of taste. This paper explores how class, gender and false pretences are ridiculed and exposed in both novels and short stories, and how laughter moves from a classical Kantian play instance to a Freudian-supported analysis of condensation and ambiguity as vehicles employed by a realist creator. The narrative often alternates between family roles and poles of power, visible and invisible laughter, as natural and changing (or hybrid) as human nature.